Numerical Investigation of the Influence of Axial Overlap of Blade Angle Slots on an Axial Flow Compressor Stability - H. Zhang; W. Liu; E. Wang; W. Chu; J. Yang; W. Zhao (Journal of Applied Fluid Mechanics, 2020)
In this paper, a numerical investigation was conducted on a subsonic compressor rotor with blade angle slot casing treatments. The purpose of the investigation is to reveal the influence of axial overlap of blade angle slot on the compressor stability. Six kinds of blade angle slot casing treatments with different axial overlap rates were investigated in this paper. The results show that with the increasing of axial overlap rates, the stall margin improvement firstly increased and then decreased. And the optimal blade angle slot can obtain 62.51% improvement of stall margin. The flow field analyses show that the bleeding flows formed inside slots can restrain the adverse tip leakage flow, which is the critical factor making the onset of the rotor stall. With the increasing of axial overlap rate of the slots, the relative position between bleeding flows in the slots and tip leakage flow plays an important role in the stall margin improvement.